A preclinical study of a novel dual-modality contrast agent in rodent models - Zhou, Xuelai; Jiang, Kangli; Han, Yuxin; Yang, Shuxu (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionGlioblastoma (GBM) represents the most aggressive and prevalent form of primary malignant brain tumor in adults, with surgical intervention being the primary treatment modality. To enhance surgical outcomes and extend patient survival, we have engineered a dual-modality MRI/FI contrast agent known as PL002 to aid in the surgical management of GBM.MethodsIn this study, an orthotopic glioma model was established in mice via intracranial injection of U-87 MG cells. Subsequently, the model animals were intravenously injected with PL002 and placed in a 7.0T magnetic resonance imaging (MRI) device to evaluate the imaging effects. After the MRI scan, fluorescence imaging techniques were employed to observe the distribution of PL002 at both the brain tissue and cellular levels. Moreover, healthy rat models were utilized to investigate the pharmacokinetic characteristics, tissue distribution, and safety profile of PL002.ResultsThe molecular structure of PL002 contains both gadolinium (Gd3+) and indocyanine green (ICG), demonstrating optimal imaging effects within the dosage range of 10-50 mg/kg, with a half-life of 2.51 to 4.87 hours. Even at relatively low concentrations in the brain, PL002 can provide stable and sustained support for MRI and fluorescence imaging for up to 72 hours. No abnormalities were observed in rats at a dosage of 100 mg/kg.DiscussionCompared to Gadavist® and ICG, PL002 provided sustained support for MRI and FI of GBM for 72 h, with a broad therapeutic window. This dual-modality contrast agent holds significant potential and promise for applications in preoperative assessment of resection margins, real-time intraoperative guidance, and postoperative verification of the extent of resection.